The natural history of hypertrophic cardiomyopathy in a large Mediterranean cohort. Issue 6 (June 2020) - Parcharidou, Despoina; Zegkos, Thomas; Ntelios, Dimitris; Panagiotidis, Theofilos; Katranas, Sotiris; Siskos, Alexandros; Meditskou, Soultana; Karvounis, Haralampos; Efthimiadis, Georgios
Abstract : Background: Hypertrophic cardiomyopathy (HCM) represents the most common inherited cardiomyopathy and it is characterized by phenotypic and genetic heterogeneity. The purpose of our study was to investigate the natural history of HCM in a large Mediterranean cohort and to identify predictors of outcomes. Methods: The clinical and echocardiographic characteristics of 690 patients with HCM were examined. The predictors of mortality and sudden cardiac events were examined during a mean follow-up of 8.5 years. Results: Asymmetrical hypertrophy was the most common among our cohort (82.9%) followed by apical hypertrophy pattern (13.6%). Atrial fibrillation was present in 22.3%, whereas nonsustained ventricular tachycardia occurred in 10.4% of the patients. During follow-up, a total of 7.4% of patients died. Specifically, 5.5% HCM patients died from cardiovascular causes, including 2.8% from heart failure and 2% from sudden death. Obstructive phenotype did not have any effect on mortality. Atrial fibrillation, ejection fraction and right ventricular systolic pressure (RVSP) were common independent predictors for overall and cardiovascular mortality. A total of 6.1% of HCM patients suffered sudden arrhythmic events and maximal wall thickness, ejection fraction, nonsustained ventricular tachycardia, syncopal episodes and, more importantly, the presence of an apical aneurysm were all independent risk factors. Conclusion: HCM is a relatively benign cardiomyopathy in Greece, similarly to other countries. Apical hypertrophy pattern is more common in Greece than in the other European countries, whereas the presence of apical aneurysm is the most important risk factor for arrhythmic events on top of the established risk factors for sudden death. Abstract : Supplemental Digital Content is available in the text